The effect of miR-155–5p on M1 polarization of Kupffer cells and immune response during liver transplantation through regulating the expression of KDM5D. (March 2023) - Song, Cangsang; Wang, Guohui; Ma, Xuejiao; Mao, Panpan; Lu, Wei; Zhang, Hanshu; Liu, Lu; Zhang, Yang; Li, Xingde
Abstract: Background: To explore the effect and its specific mechanism of miR-155–5p on M1 polarization of Kupffer cells (KCs) and immune response in liver transplantation (LT) through KDM5D. Methods: Primary KCs were isolated from Wistar rats and identified by cell culture, ink-swallowing test and flow cytometry. The cells identified as KCs were induced into LT acute rejection (AR) model cells by LPS/IFN-γ, flow cytometry was used for cell sorting and apoptosis detection. Enzyme-linked immunosorbent assay (ELISA) kit was used to detect the levels of inflammatory factors, macrophages and liver function markers. RT-qPCR detected the expression of miR-155–5p and KDM5D mRNA. The protein expression of KDM5D was detected by Western blot. Dual luciferase reporter gene experiment verified the targeting relationship between miR-155–5p and KDM5D. Results: The separated KCs adhered after being cultured for 24 h, had pseudopodia and phagocytosis, and the proportion of F4/80 positive cells was more than 90%. The expression of miR-155–5p was increased in LPS/IFN-γ-induced KCs. And knockdown of miR-155–5p inhibited H3K4me3 and H3K27me3 of TNF-α promoter, M1 polarization of KCs and the immune response of AR model cells by upregulating KDM5D. In animal experiments, knockdown of miR-155–5p was found to inhibit liver damage and immune response in rats with allogeneic orthotopic LT. Conclusion: These results confirmed that miR-155–5p inhibited M1 polarization of KCs induced by LPS/IFN-γ, thereby alleviating AR and liver function impairment after LT by upregulating KDM5D. Highlights: miR-155–5p increases in LPS/IFN-γ-induced KCs. Knockdown miR-155–5p in LPS/IFN-γ-induced KCs inhibits M1 polarization of KCs, the production of pro-inflammatory cytokines and cell apoptosis rate. miR-155–5p regulates immune response of AR in LT by targeting KDM5D. Knockdown of miR-155–5p significantly inhibits the levels of H3K4me3 and H3K27me3 of TNF-α promoter, inhibits the immune response of rats and alleviate liver injury.